Economic analysis of coniferous silviculture in Poland : profitability comparison between Poland and Lithuania - Bis, Aleksandra (SLU/Southern Swedish Forest Research Centre, 2009)
Cash flow analysis from pine and spruce stands on I and II site index was made basing on data collected from three Polish forestry districts. Data obtained from districts allowed to calculate NPV, IRR and FR economical indicators for the years 2001 and 2006. Economic outcomes were calculated by discounting costs and incomes with 3% discount rate. Additionally, calculations with administration costs were made. Furthermore, a part of the report compares Polish and Lithuanian economical outcomes in 2006 from pine and spruce stands of the same productivity. The following criteria were defined for all pine and spruce stands: the height of the pines reaches 24 meters and spruce 28 meters at the age of 100 years. Only state owned productive forests were investigated. The next accepted step was making the forest management programme as similar as possible to the forestry practice in both countries. Project investigations revealed that pine stands in Poland on most common site index are not profitable according to NPV and IRR criterion with and without adding administration costs. However spruce profitability reaches more than 4 percent without taking into account administration costs. After adding administration costs it went down into 2.5 percent. For Polish pine and spruce stands forest rent remains positive with and without administration costs. Despite increasing prices for timber assortments, profitability did not increase significantly between years 2001 and 2006 due to increase of labour costs. Comparison of Polish and Lithuanian silviculture regimes revealed that Polish pine stands are much less profitable than Lithuanian. The reason behind this lies in a higher number of treatments required and implemented during rotation. However Polish spruce stands with more treatments implemented but a 25 years longer rotation have a higher profitability in Poland. The main reason for this is a much higher spruce productivity in Poland than in Lithuania and higher wood prices. Furthermore administration costs are more severe in Poland, which decreases profitability as compared to Lithuania. In general, the report results lead to the conclusion that only those entrepreneurs which are willing to freeze their capital for a long time in bringing low interest rate investments can invest money in Polish and Lithuanian forestry.